Using the museum education in teaching kindergarten children from the point of view of kindergarten teachers in Medina city - Kurdi, Esraa Emad; Belgoun, Kawther Jamil (Journal of Educational and Psychological Sciences, 2023)
This study aims to know the importance, reality and obstacles of using museum education in teaching kindergarten children from the point of view of kindergarten teachers in Medina city. The researcher used the survey descriptive methodology, and the study sample consisted of (256) female teachers, selected in a random manner from the original school community of all kindergarten teachers in the state and private schools in Medina city, and the study tool was survey. The study reached to some findings as follows: the study sample members represented in the kindergarten teachers are highly agreed with the importance of museum education in teaching the kindergarten children. Using the museum education in teaching kindergarten children was moderate from the point of view of kindergarten teachers. According to the high acceptance of the study sample members on the museum education usage obstacles in teaching the kindergarten children, among the most prominent obstacles are (the high financial costs for establishing a corner for the museum in the kindergarten and the great numbers of children in the number of children in the classroom, limits the teacher from conducting the museum visits). The findings revealed that there were statistically significant differences in regard with the study sample’s vocabulary for the academic qualification as the differences were in favor of the higher education. The findings also revealed that there were no differences regarding the experience years and type of kindergarten. The study recommended to hold training courses for kindergarten teachers how to activate museum education in teaching kindergarten children.in addition, providing the required financial allocations to establish a museum corner in the kindergarten and to reduce the number of children in the classrooms to let the teacher conduct the museum visits.
Keywords: Museum education; kindergarten children; kindergarten teachers